TEACHING WRITING IN EFL CLASSROOM - Nanik Sri Rahayu (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
Teaching writing in EFL classroom sometimes becomes a problem for the teacher. They are confused how to handle the class and where they have to start or end the class to fulfill the students’ need. Incomplete language rule, lack of vocabulary, inadequate information to write, and the different competence in writing are some reasons why teaching writing sometimes leads to the teaching of writing not for writing. To avoid this problem, a teacher should know what they should do before, during and after the writing class to make the students to become a better writer.